Effect of ZrO2 addition on the NTC thermistor characteristics based on Fe2O3 from the mineral yarocyte - Rosi Selfia Putri; Ratnawulan Ratnawulan; Dani Gustaman Syarif (Department of Physics – Universitas Negeri Padang UNP, 2017)
Ceramic pellet has been made for the Negative Thermal Coefficient (NTC) thermistor from Fe2O3 base material of yarosite mineral. The powder of Fe2O3and ZrO2 is mixed and then crushed until homogeneous for ± 30 minutes. The mixture of the powder is pressed with 60 ton/cm2 to form a pellet on the 8 mm diameter mold. The pellets are sintered at a temperature of 1200oC for 3 hours in a furnace with atmospheric air. The pellet from the sintering process is coated with silver as an electrode. Next will be characterized using XRD (X-Ray Diffractometer), SEM (Scan Electron Microscope) and electrical characterization. Based on the results of XRD analysis it is known that the ceramics formed with the addition of ZrO2 0% doping, ZrO2 1% and ZrO2 3% have hexagonal hematite structure. Grain size based on SEM analysis, for each addition of 0% doping, ZrO2 1% and ZrO2 3% respectively is 10.81 μm; 11.51 μm and 10.24 μm. Results of measurement of electrical resistance, thermistor constant value is 3322 K, 3645 K and 5873 K. Conclusion in this study is the addition of ZrO2 does not affect the crystal structure formed based on the analysis using XRD. Addition of ZrO2 into Fe2O3 ceramic causes the grain size is relatively unchanged significantly. Based on the measurement of lstric resistance, the greater the ZrO2 addition concentration, the greater the resistance value at room temperature and the resulting thermistor constant